Ältere niederländische und polnische Bibelübersetzungen - Krajcarz, Mariusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
The article is an attempt at a chronological presentation of the most important old and complete translations of the Bible by the time and including the Protestant Reformation in both compared languages. As for the Dutch language, eight Biblical translations have been analysed with Protestant translations prevailing (5). On the other hand, Polish is represented by five old translations of the Scriptures with a slight advantage of Protestant translations (3) over Catholic ones (2). Translations of the Bible largely affected the language and the style of the Scriptures. It is worth emphasizing that they were most influenced by the Protestant Staatenbijbel (1637) in the then Netherlands and by the Jakub Wujek Bible (1599) in Poland.